Hubungan Pengetahuan Ibu Hamil Trimester III tentang Anemia dengan Kepatuhan Konsumsi Tablet Fe di Puskesmas Perawatan Namrole Kec. Namrole Kab Buru Selatan Tahun 2023 - Saripina Girsang S; Eva Dona Sinaga; Kamelia Sinaga (Lembaga Pengembangan Kinerja Dosen, 2024)
Anemia in pregnancy is known to occur in pregnant women when iron levels in their blood are low. Pregnant women are said to have anemia if their hemoglobin (Hb) level is <11 grams/dl in the first and third trimesters of pregnancy, in contrast to the second trimester hemoglobin (HB) level <10.5 grams/dl. The aim of the research was to determine the relationship between third trimester pregnant women's knowledge about anemia and compliance with consuming Fe tablets at the Namrole Care Health Center in 2023. This research was quantitative in nature with an analytical survey with a cross sectional research design, which was conducted in the Namrole Maluku Health Center Work Area. The population in this study were all 32 pregnant women in the third trimester. The sampling technique used is Total Sampling. Bivariate analysis uses the Chi Square test with a confidence level of 95%. shows that the p value = 0.000 which means less than A = 0.005, so it can be concluded that there is a significant relationship between the knowledge of third trimester pregnant women about anemia and compliance with consuming Fe tablets at the Namrole Nursing Community Health Center, Kec. Medan Johor in 2023.